Perspective of Melatonin-Mediated Stress Resilience and Cu Remediation Efficiency of Brassica juncea in Cu-Contaminated Soils - Mir, Anayat Rasool; Alam, Pravej; Hayat, Shamsul (Frontiers in Plant Science, 2022)
The present study evaluated the influence of melatonin (MEL) on copper toxicity in terms of morphophysiological, microscopic, histochemical, and stress resilience responses in Brassica juncea. Different levels of Cu (0, 30, and 60 mg kg–1) were given in air-dried soil, and 25 days after sowing (DAS), plants were sprayed with 30, 40, or 50 μM of MEL. The results demonstrated that under Cu stress, a significant amount of Cu accumulated in plant tissues, particularly in roots than in upper ground tissues, thereby suppressing the overall growth as evidenced by decrease in tolerance index and photosynthesis and increase in oxidative stress biomarkers (reactive oxygen species, malondialdehyde, and electrolyte leakage content) and cell death. Interestingly, the follow-up treatment of MEL, mainly 40 μM, efficiently improved the physio-biochemical and growth parameters, sugar accumulation, and metabolism. The potential of MEL in modulating Cu stress is attributed to its involvement in enriching the level of nutrient and improving chloroplast and stomatal organization besides lowering oxidative stress via enhanced levels of antioxidants. MEL improved the Cu reclamation potential in plants by enhancing Cu uptake and its translocation to aerial tissues. Principal component analysis showed that most of the morphophysiological and growth attributes were positively linked with MEL and negatively related to Cu levels, whereas all the stress-enhancing attributes showed a strong relationship with excessive Cu levels in soils. The present study suggested that MEL has the potential to improve growth and photosynthesis resulting in improved stress resilience under Cu stress along with increased remediation capability of mustard for remediation of Cu-contaminated soils.